2005
DOI: 10.1002/path.1814
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulated expression of ADAM17 in human colon carcinoma: co‐expression with EGFR in neoplastic and endothelial cells

Abstract: The ADAM17 metalloproteinase (a disintegrin and metalloprotease 17) controls epidermal growth factor receptor (EGFR) activation through regulated shedding of EGFR ligands. With the advent of new therapeutic options targeting EGFR signalling in colon carcinoma, it was decided to determine ADAM17 status in relation to clinico-pathological parameters and EGFR status. To this end, a series of 39 colon carcinomas were analysed. Immunohistochemistry and immunofluorescence were used to localize ADAM17, EGFR, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 27 publications
7
98
0
2
Order By: Relevance
“…As these two tests may yield a lower number of positive cases, one could argue that some of the negative cases of this report could have been positive if they were tested by Ventana 3C6 or the Zymed test used in our current study. Four antibodies were used in the recent studies of EGFR expression and according to our study, showed that they were not equivalent in terms of the percentage of positive cells (Table IV) (10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…As these two tests may yield a lower number of positive cases, one could argue that some of the negative cases of this report could have been positive if they were tested by Ventana 3C6 or the Zymed test used in our current study. Four antibodies were used in the recent studies of EGFR expression and according to our study, showed that they were not equivalent in terms of the percentage of positive cells (Table IV) (10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…ADAM-10 acts through EGFR ligand shedding leading to gastric cell proliferation [151][152][153]. In colon carcinomas, ADAM-17 is overexpressed independently of tumour stage or grade and is involved in tumour growth and angiogenesis possibly via an autocrine/paracrine pathway implicating EGFR [154].…”
Section: Gastric and Colon Carcinomamentioning
confidence: 99%
“…17 Proteins (50 mg) were separated by electrophoresis on 10% polyacrylamide gels and transferred onto nitrocellulose membranes (0.45 mm porosity; Bio-Rad, Hercules, CA, USA) using Trans-blot apparatus (Bio-Rad). After blocking, membranes were incubated with primary antibodies against E-cadherin endodomain (clone 4A2C7, dilution 1:1000; Zymed) and N-cadherin endodomain (clone 3B9, dilution 1:250; Zymed), and then with a horseradish-peroxidase conjugated, goat anti-mouse antibody (dilution 1:1000; Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Immunoblot Analysismentioning
confidence: 99%